Enhancement of Polyribosome Formation and RNA Synthesis of Gibberellic Acid in Wounded Potato Tuber Tissue - Wielgat, Bernard (1979)
As part of a more detailed study on plant tumorigenesis, the action of gibberellic acid (GA(3)) in wounded potato tuber tissues as a model system has been evaluated. GA(3) stimulates total RNA synthesis in wounded tissues, the optimal concentration being 0.1 micromolar. The responsiveness of the tissue toward the hormone develops with time after wounding. Whereas freshly wounded tissue does not respond at all to the hormone, it becomes competent after about 6 hours, the competence being maximal after 1 day of wound healing. GA(3) enhances the formation of polyribosomes in wounded tissues and stimulates the synthesis of both ribosomal RNAs, transfer RNAs, 5S RNA, and a fraction, which in sucrose density gradients sediments between 18S rRNA and 5S RNA. This fraction contains presumptive mRNA. The hormone, then, is somehow recognized by wounded potato tissue in a time-specific way; the signal is transferred to the genome and triggers the synthesis of various RNA species.